Rozwiąż równania:
a) 2x²+(x+5)²−2(x+7)²=2(3x−72,5)+(x−6)²
b) (x+3)²−(x−5)²=16(x−1)
c) (x−3)(x−2)(x+2)=(x−1)³+6
d) 3x−3=2√2x+2√2
e) x(√2+3)=2√2+4x
f) 3x=2+√5+x√5
g) x+√2=π−3x
h) (x+√2)(1−√2)=−1
i) (√5−x)(2+√5)=3√5+7
j) (3−√3)(3x+√3)=0
k) (1−2√3)(x−1)=2√3−1
Bardzo proszę pomózcie:(

2

Odpowiedzi

2010-03-21T13:51:54+01:00
Rozwiązania w załącznikach!:)
2010-03-21T13:58:58+01:00
A)
2x²+(x+5)²−2(x+7)²=2(3x−72,5)+(x−6)²
2x²+x²+10x+25-2(x²+14x+49)=6x-145+x²-12x+36
3x²+10x+25-2x²-28x-98=-6x-19+x²
x²-x²-18x+6x=-19+73
-12x=54 /:(-12)
x=-4,5

b)
(x+3)²−(x−5)²=16(x−1)
x²+6x+9-x²+10x-25=16x-16
16x-16x=-16+16
0=0

c)
(x−3)(x−2)(x+2)=(x−1)³+6
(x-3)(x²-4)=x³-3x²+3x-1+6
x³-4x-3x²+12=x³-3x²+3x+5
-4x-3x=5-12
-7x=-7 /:(-7)
x=1